(untitled) (Management Dynamics, 2022)
Human resource is the fundamental resources of the organization, which determine the performance of the organization as well as gives the life to the other resources and the organization. This study focuses on assessing the role of employee performance-driven practices on employees’ performance in Nepalese commercial banks. This study utilizes the quantitative research approach with a causal-comparative and analytical research design. The sample of the study is 385 respondents from Kathmandu valley. Reliability analysis, descriptive statistics, correlation, and regression analysis are utilized to draw the conclusion. Evidence indicates that leadership, working environment, motivation, and job satisfaction positively and significantly affect employee performance in the Nepalese banking sectors. Finally, this study suggests banks provide excellent leadership opportunities, a good working environment to the employees, rich motivation, and focus on job satisfaction through intrinsic and extrinsic reward systems that positively contribute to the bank employees’ performance and might lead to downsizing employee turnover also.